Human anatomy in ancient Indian sculptures of Gandhara art illustrating the fasting Buddha - Abrahams, Peter (2019)
The present article intends to report the surface anatomical features in the three fasting Buddha sculptures and also tries to understand the anatomical knowledge of these ancient Indian sculptors by observing the digital images of the sculptures of the Gandhara art depicting the fasting Buddha. Close examination of the colour 2D digital photographs of the fasting Buddha which are available freely at Google Cultural Institute, the British Museum and the Metropolitan Museum web portals. Our observations demonstrate that the bones and joints of the thoracic cage, pectoral girdle, the extremities, particularly the upper limb, the skull and the pelvis were distinctly shown in the sculptures. Muscles of the neck (sternocleidomastoid, trapezius), shoulder (deltoid), thoracic cage (pectoralis major), limbs (arm and forearm), and anterior abdominal wall were clearly carved into the sculptures. The trachea was correctly placed in the neck. The boundaries of the axilla, and triangles of the neck were also clearly seen. Our observations demonstrate that ancient Indian artists of the Gandhara region had a basic knowledge of human anatomy, especially surface anatomy and musculoskeletal features. They also possessed knowledge of the approximate size and position of the bones, joints and muscles, including their approximate origin and insertion points. However, certain errors of anatomical knowledge including an extra number of ribs and a segmented sternum were noticed. Further, they also seemed to have some basic ideas about the physiological changes that occur during starving, as it is evident in the Buddha sculptures, which are skinny and emaciated.